Assessment of knowledge, attitude, and practices of biomedical waste management among health care workers in a tertiary care hospital, Chengalpattu, Tamilnadu, India - Savetha Palaneswamy; Akshada Srikumar; Iyanar Kannan; Thenmozhivalli Pitchai Rathinam (Occupational Health and Safety Society of Nepal, 2024)
Introduction: Bio-medical waste (BMW) means any solid and/or liquid waste including its container and any intermediate product, which is generated during the diagnosis, treatment, or immunization of human beings or animals. Inadequate and inappropriate knowledge of handling healthcare waste may have serious health consequences and a significant impact on the environment. Thus, the study aims to assess the knowledge, attitude, and practice of biomedical waste management among healthcare workers from different strata in the hospital.  Methods: This was a cross-sectional study involving 383 participants conducted between June 2022 to October 2022, A structured, close-ended, self-administrated questionnaire was used to collect the data. The data were analyzed using R studio and presented as frequencies and percentages. The association between different variables was analyzed by the chi-square test.  Results: Most of the doctors (41.3%) and nurses (41.5%) had very good knowledge of Bio-Medical Waste Management (BMWM) but only 23.1% of laboratory technicians and housekeeping staff 18.2% showed very good knowledge. All the participants had a very good attitude (69.2% to 82.6%) towards BMWM but it needs some improvement concerning reporting needle stick injuries and taking Post-exposure prophylaxis (PEP). More than 80 % of participants were immunized against Hepatitis B and followed the appropriate practice of BMWM except for wearing adequate personal protective equipment (PPE) while handling BMW. Knowledge and good attitude were observed to increase with experience.  Conclusion: From the study, it is identified that knowledge regarding BMWM is inadequate among the healthcare professions. It is concluded that there should be adequate training among the HCWs about BMWM like video lectures, symposiums, quiz programs, and role play that can help them update their knowledge.